MANAGEMENT METHODS OF PRODUCTION EXPENDITURE - Shulha, A. V.; Semeiko, Ya. V. (Science and Transport Progress, 2008)
The problem of search of the methods of management of production expeuditures has been examined and some ways of its solving have been proposed.